Respuesta :
6n + 9 = -3n + -21 + -6
Reorder the terms:
9 + 6n = -21 + -6 + -3n
Combine like terms: -21 + -6 = -27
9 + 6n = -27 + -3n
Solving
9 + 6n = -27 + -3
Add '3n' to each side of the equation.
9 + 6n + 3n = -27 + -3n + 3n
Combine like terms: 6n + 3n = 9n
9 + 9n = -27 + -3n + 3n
Combine like terms: -3n + 3n = 0
9 + 9n = -27 + 0
9 + 9n = -27
Add '-9' to each side of the equation.
9 + -9 + 9n = -27 + -9
Combine like terms: 9 + -9 = 0
0 + 9n = -27 + -9
9n = -27 + -9
Combine like terms: -27 + -9 = -36
9n = -36
Divide each side by '9'.
n = -4
Simplifying
n = -4
Answer:
n = - 4
Step-by-step explanation:
6n + 9 = -3n - 21 - 6
6n + 3n = - 21 - 6 - 9
9n = - 27 - 9
9n = -36
n = -36/9
n = - 4